Glasdegib plus intensive or non-intensive chemotherapy for untreated acute myeloid leukemia: results from the randomized, phase 3 BRIGHT AML 1019 trial - Sekeres, Mikkael A; Montesinos, Pau; Novak, Jan; Wang, Jianxiang; Jeyakumar, Deepa; Tomlinson, Benjamin; Mayer, Jiri; Jou, Erin; Robak, Tadeusz; Taussig, David C; Dombret, Hervé; Merchant, Akil; et al. (Leukemia, 2023)
This is the primary report of the randomized, placebo-controlled phase 3 BRIGHT AML 1019 clinical trial of glasdegib in combination with intensive chemotherapy (cytarabine and daunorubicin) or non-intensive chemotherapy (azacitidine) in patients with untreated acute myeloid leukemia. Overall survival (primary endpoint) was similar between the glasdegib and placebo arms in the intensive (n = 404; hazard ratio [HR] 1.05; 95% confidence interval [CI]: 0.782-1.408; two-sided p = 0.749) and non-intensive (n = 325; HR 0.99; 95% CI: 0.768-1.289; two-sided p = 0.969) studies. The proportion of patients who experienced treatment-emergent adverse events was similar for glasdegib versus placebo (intensive: 99.0% vs. 98.5%; non-intensive: 99.4% vs. 98.8%). The most common treatment-emergent adverse events were nausea, febrile neutropenia, and anemia in the intensive study and anemia, constipation, and nausea in the non-intensive study. The addition of glasdegib to either cytarabine and daunorubicin or azacitidine did not significantly improve overall survival and the primary efficacy endpoint for the BRIGHT AML 1019 phase 3 trial was not met. Clinical trial registration: ClinicalTrials.gov: NCT03416179.
Keywords: Leukemia, Myeloid, Acute; Cytarabine; Antineoplastic Combined Chemotherapy Protocols; akutní myeloidní leukemie; Azacitidine; Nausea; nauzea; Daunorubicin; Anemia; protokoly protinádorové kombinované chemoterapie; anemie; cytarabin; Humans; lidé; azacytidin; daunomycin